The problem of political marketing - Savigny, Heather (Continuum, 2008)
"Based upon analysis of existing theoretical literature and current political practice this book addresses both the use of marketing and its impact (real and potential) upon democracy by answering the following: * Why have politicians adopted political marketing? What are the contextual factors that have led to this? * How does the political marketing literature model this activity? * What are the underlying assumptions of these models * How does political marketing affect democracy? * How is political marketing best conceptualised and understood in light of this critical analysis?"--Bloomsbury Publishing